The music editions in the Scott Collection of the Music Library of the University of Stellenbosch before and up to 1800, excluding church music : an annotated catalogue with some notes on printers and publishers - Du Toit, Elizabeth (Stellenbosch : Stellenbosch University, 2012)
Thesis (MMus)--Stellenbosch University, 1993.